Application of Internet of Things (IoT) Technology Automatic Plant Watering Using Arduino Program on Corn Plants of Sadar Tani Farmers Group - Mimmy Sari Syah Putri; Saib Suwilo; Aghni Syahmarani; Putri Cahaya Situmorang; Alberto Tondang (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
The technology of the Internet of Things (IoT) is advancing and being implemented in a variety of sectors, including agriculture. The Sadar Tani farmer group's automatic plant watering system for maize plants is the focus of this research, which investigates the application of IoT technology. The primary controller of this system is an Arduino device, which is connected to a communication module and soil moisture sensor to transmit data in real-time. The water pump is automatically activated to irrigate the plants until the humidity level returns to normal when the soil moisture level falls below the specified limit. This implementation has yielded enhanced corn plant health, reduced farmer workload, and increased water use efficiency. Furthermore, this system enables the remote surveillance of crop conditions, which offers supplementary advantages in the management of larger agricultural lands. As a result, the implementation of IoT technology offers a viable solution to the issue of watering plants on expansive agricultural land, in addition to promoting precision agriculture that is more environmentally favorable and sustainable. This research has the potential to serve as a reference for future development in the application of similar technology to other crops and the enhancement of features to optimize agricultural yields.